OBJECT-ORIENTED PROGRAMMING ROBOTIC BALL ORBOTIX SPHERO - LAVRINCIK, Jan (Trends in education, 2014)
The article deals with object-oriented programming applications MacroLab orbBasic a robotic ball Orbotix sphere. Focusing in particular on the possibility of visual and physical demonstrations of basic algorithms, movement, spatial orientation, and the timer cycles. In the conclusion, the polemic over the use in the teaching of algorithms and programming in upper secondary education.
Keywords: object-oriented programming; Orbotix Sphero; MacroLab; orbBasic.